What the Function?

Algebra Level 4

Let f : R C f:\mathbb{R} \mapsto \mathbb{C} be defined as f ( x ) = ln π ( ln x ) 2 + π 2 ( ln x π i ) x + f(x) = \dfrac{\ln{\pi}}{(\ln{x})^2+\pi^2}\cdot (\ln{x}-\pi i) \quad \forall x^+ .

If f ( 2 ) = log a π f(2) = \log_a\pi find a a , where a a is a real number.


The answer is -2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Jan 19, 2017

f ( 2 ) = log a π a f ( 2 ) = π e ln a f ( 2 ) = π ln a f ( 2 ) = ln π ln a = ln π ( ln 2 ) 2 + π 2 ln π ( ln 2 π i ) = ( ln 2 ) 2 + π 2 ln 2 π i = ( ( ln 2 ) 2 + π 2 ) ( ln 2 + π i ) ( ln 2 π i ) ( ln 2 + π i ) = ( ( ln 2 ) 2 + π 2 ) ( ln 2 + π i ) ( ln 2 ) 2 + π 2 = ln 2 + π i a = e ln 2 + π i = e ln 2 e π i = 2 ( 1 ) = 2 \begin{aligned} f(2) & = \log_a \pi \\ \implies a^{f(2)} & = \pi \\ e^{\ln a \cdot f(2)} & = \pi \\ \ln a \cdot f(2) & = \ln \pi \\ \ln a & = \ln \pi \cdot \frac {(\ln 2)^2 + \pi^2}{\ln \pi (\ln 2 - \pi i)} \\ & = \frac {(\ln 2)^2 + \pi^2}{\ln 2 - \pi i} \\ & = \frac {\left((\ln 2)^2 + \pi^2\right)(\ln 2 + \pi i)}{(\ln 2 - \pi i)(\ln 2 + \pi i)} \\ & = \frac {\left((\ln 2)^2 + \pi^2\right)(\ln 2 + \pi i)}{(\ln 2)^2 + \pi^2} \\ & = \ln 2 + \pi i \\ \implies a & = e^{\ln 2 + \pi i} = e^{\ln 2} e^{\pi i} = 2(-1) = \boxed{-2} \end{aligned}

@Chew-Seong Cheong You might want to change the final answer in your solution. There's a typo.

Akeel Howell - 4 years, 4 months ago

Log in to reply

Thanks. I definitely got to change it.

Chew-Seong Cheong - 4 years, 4 months ago

Log in to reply

You're welcome.

Akeel Howell - 4 years, 4 months ago
Akeel Howell
Jan 18, 2017

We have that f ( x ) = ln π ( ln x ) 2 + π 2 ( ln x π i ) x 0 f(x) = \dfrac{\ln{\pi}}{(\ln{x})^2+\pi^2}\cdot (\ln{x}-\pi i) \quad \forall x \neq 0 and f ( 2 ) = log a π f(2) = \log_a\pi .

So f ( 2 ) = ln ( π ) ( ln 2 ) 2 + π 2 ( ln 2 π i ) = ( ln 2 π i ) ln π ( ln 2 + π i ) ( ln 2 π i ) . f(2) = \dfrac{\ln(\pi)}{(\ln{2})^2 + \pi^2} \cdot (\ln{2}- \pi i) = \dfrac{(\ln{2}-\pi i) \cdot \ln{\pi}}{(\ln{2}+\pi i)(\ln{2}-\pi i)}.

Since ( ln 2 ) 2 + π 2 = ( ln 2 + π i ) ( ln 2 π i ) f ( 2 ) = ln π ln 2 + π i = ln π ln ( 2 ) = log ( 2 ) π = ln π ln ( 2 ) {(\ln{2})^2+\pi^2 = (\ln{2}+\pi i)(\ln{2}-\pi i)}\\ \implies f(2) = \dfrac{\ln{\pi}}{\ln{2}+\pi i} = \dfrac{\ln{\pi}}{\ln{(-2)}} = \log_{(-2)}\pi = \dfrac{\ln{\pi}}{\ln{(-2)}}

1 ln ( 2 ) = 1 ln a ln ( 2 ) = ln a a = 2 \therefore \dfrac{1}{\ln{(-2)}} = \dfrac{1}{\ln{a}} \implies \ln{(-2)} = \ln{a} \\ \therefore a = \boxed{-2} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...